Microglia control vascular architecture via a TGFβ1 dependent paracrine mechanism linked to tissue mechanics - Tejasvi Dudiki (Nature Portfolio, 2020)
During development and pathologies of the central nervous system, blood vessels are closely connected with the innate immune cells, microglia. Here, the authors report that microglia adjust their angiogenic program to shape blood vessels and may depend on tissue stiffness.